Manifestation of Consciousness - Krakauskas, Edmundas (Problemos, 1975)
Physical labour induced changes in the functions of organs of the human body, and these, in tum, caused changes in the functions of the brain. These served as the basis for a new social function of understanding the world. The brain functions enable man to comprehend the experienced reality. The term “consciousness” embraces process of sensation, feeling, mood, perception, thinking, both conscious and unconscious. Consciousness is the product of interaction between the brain functions and social material human activity. Consciousness is a property of very active social beings, the human ones. Consciousness, having originated in the process of interaction of forms of matter, depends on matter. That is why it should be explained in terms of interaction of forms of matter.